Break-up length of liquid jets produced by short nozzles. (February 2018) - Etzold, M.; Deswal, A.; Chen, L.; Durst, F.
Highlights: Experiments on liquid jet break-up showed significant deviations to existing and accepted data from the literature. The reasons for these deviations were found out to be the properties of the gas boundary layers around the liquid jets. A modification of a classical model incorporating gas boundary layer effects is presented and good agreement of this modified model with the measurements is obtained. The decreasing branches of the experimental stability curves were found to be related to the second wind-induced break-up regime, since the corresponding criteria were fulfilled. Abstract: Numerous experimental studies and theoretical investigations related to the break-up length of liquid jets can be found in the literature. Experimental results, given in this paper and obtained with nozzles having a very small length-to-diameter ratio, showed poor agreement with existing theoretical and experimental data. It was found that the discrepancies can be explained by differences in the ambient Reynolds number ranges covered. Therefore, the properties of the ambient gas boundary layer around the liquid jet had to be taken into account to describe theoretically the experimental stability curves. A modification of the model of Sterling and Sleicher (1975) is proposed, which involves treating their constant correction factor accounting for ambient viscous effects of 0.175 as a variable of the jet axial coordinate with 0.189 z g * − 0.5 where z g * = z ν g / ( U a 2 ) and z, νg, U and a are the axial distance from the jet origin, the kinematic ambient viscosity, the jet velocity and the jet radius, respectively. The decreasing branches of the experimental stability curves were found to be related to the second wind-induced jet break-up regime, since the curves coincide and show no dependence on the nozzle diameter. The critical points of the stability curves were found to lie within a small range of ambient Weber numbers, also indicating the onset of second wind-induced break-up. One of the investigated nozzles showed distinct deviations from the existing model and the proposed modification. In this case, further investigations are required for clarification.